Research on pseudomonas bacterial epiphytes in Colorado - Garrett, K.A.; Schwartz, Howard F. (1987)
In 1986, 5 commercial bean sites near Holyoke (Colorado, USA) were treated with 4 sprays of cupric hydroxide every 7 to 10 days beginning at least 2 wk. before flowering to (1) sample for the presence of Cu resistance in naturally-occurring epiphytic populations of Pseudomonas syringae pv. syringae and P. syringae pv. phaseolicola; and (2) determine relationships between leaf, flower, pod, and seed epiphytic populations of these bacteria. Of the 430 epiphyte isolates evaluated, every P. syringae pv. syringae isolate exhibited greater Cu resistance than every P. syringae pv. phaseolicola. Preliminary analysis indicates that epiphytic flower populations may be useful predictors for their epiphytic pod populations the following wk. (CIAT)